2020
DOI: 10.1681/asn.2019100987
|View full text |Cite
|
Sign up to set email alerts
|

Crucial Role of AIM/CD5L in the Development of Glomerular Inflammation in IgA Nephropathy

Abstract: BackgroundIgA nephropathy (IgAN) begins with aberrant IgA deposition in glomeruli, progresses to IgM/IgG/complement codeposition, and results in chronic inflammation and glomerular damage. However, the mechanism that drives such phlogogenic cascade has been unclear. Recently, apoptosis inhibitor of macrophage (AIM) protein was shown to modulate macrophages’ function in various pathologic conditions, thereby profoundly affecting the progression of renal disorders, including AKI. A spontaneous IgAN model, groupe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…IgAN progression is influenced by the confluence of genetic and environmental factors and it is characterized by the presence of glomerular deposition of immune complexes, comprised of IgA1, together with IgG, IgM, and C3 of the complement system [ 59 ]. These immune deposits cause persistent inflammatory immune responses, which associate with enhanced macrophage infiltration and matrix expansion, which together lead to further glomerular damage [ 47 ]. In blood, CD5L binds to IgM pentamers, which stabilize and protect it from renal excretion [ 50 , 51 ].…”
Section: Cd5l In Sterile Inflammation-driven Pathogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…IgAN progression is influenced by the confluence of genetic and environmental factors and it is characterized by the presence of glomerular deposition of immune complexes, comprised of IgA1, together with IgG, IgM, and C3 of the complement system [ 59 ]. These immune deposits cause persistent inflammatory immune responses, which associate with enhanced macrophage infiltration and matrix expansion, which together lead to further glomerular damage [ 47 ]. In blood, CD5L binds to IgM pentamers, which stabilize and protect it from renal excretion [ 50 , 51 ].…”
Section: Cd5l In Sterile Inflammation-driven Pathogenesismentioning
confidence: 99%
“…Interestingly, although glomerular IgA deposition was also found in CD5L-deficient gddY mice, these animals were protected against renal injury due to the absence of IgG, IgM and C3 deposition. Thus, CD5L is essential for binding of IgM and/or IgG to previously deposited IgA to promote leukocyte infiltration, glomerular and interstitial fibrosis, extracellular matrix expansion, and increased expression of the proinflammatory genes Il-1β, IL-6, and TNF-α [ 47 ], which together enhance chronic renal damage.…”
Section: Cd5l In Sterile Inflammation-driven Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, it may facilitate IgAN progression. Blockage of AIM deposition or disassociation from IgM/IgG might therefore be a new therapeutic target in IgAN treatment [54].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was demonstrated that AIM was required for the overall inflammatory glomerular injury following IgA deposition in grouped ddY mice. Based on this, it was assumed that AIM might play a significant role in the formation of ICs, facilitating disease progression 162 . Therefore, blockage of AIM deposition presents to be a novel target in the treatments of IgAN.…”
Section: Therapeutic Strategies With An Updated Pathophysiological Pementioning
confidence: 99%